2006
DOI: 10.1002/jssc.200500492
|View full text |Cite
|
Sign up to set email alerts
|

Molecular imprinting of natural flavonoid antioxidants: Application in solid‐phase extraction for the sample pretreatment of natural products prior to HPLC analysis

Abstract: As shown in the past years, SPE based on molecularly imprinted polymers (MIPs) may provide significant enhancement of selectivity in sample preparation and analyte preconcentration. The objective of this work was the fabrication of MIPs for the specific adsorption of rutin and quercetin. The two flavonoids were used as the template molecules for the preparation of MIP phases in a self-assembly (noncovalent) approach. The produced MIPs were validated with regard to the imprinting efficiency as media for LC and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 36 publications
2
33
0
2
Order By: Relevance
“…Compared to imprinting factors of phenol and BPA, it was observed that BPA was specifically retained on polymer DM. In agreement with the earlier work [5,11,12] the highest imprinting factors were obtained in mobile phases containing higher percentage of ACN (90%), where nonspecific hydrophobic interactions are weaker, than in mobile phases with lower concentrations of ACN. When the percentage of ACN was 40% in the mobile phase the retention of both phenol and BPA was somewhat higher than the retention at 50% ACN.…”
Section: Evaluation Of Mips As Hplc Stationary Phasessupporting
confidence: 92%
“…Compared to imprinting factors of phenol and BPA, it was observed that BPA was specifically retained on polymer DM. In agreement with the earlier work [5,11,12] the highest imprinting factors were obtained in mobile phases containing higher percentage of ACN (90%), where nonspecific hydrophobic interactions are weaker, than in mobile phases with lower concentrations of ACN. When the percentage of ACN was 40% in the mobile phase the retention of both phenol and BPA was somewhat higher than the retention at 50% ACN.…”
Section: Evaluation Of Mips As Hplc Stationary Phasessupporting
confidence: 92%
“…Even though the molecular structures of the flavonoids are not ideal for molecular imprinting, as the presence of several OH groups in the polyphenolic structure could be the source of hydrogen bonding and nonlocalised electrostatic interactions between the OH groups, some attempts have been made in this direction. The objective of the work of Theodoridis et al was to fabricate molecularly imprinted polymers for the specific adsorption of rutin and quercetin [76]. The two flavonoids were used as the template molecules for the preparation of polymer phases.…”
Section: Clean-up -Isolationmentioning
confidence: 99%
“…Quercetin has now become the topic of increasing interest based on its various bioactivities such as inoxidability, antiviral property, antitumor and adjusting the immune function [18], as well as its chemical applications, e.g., quercetin is immobilized on silica gel and used as a solid-phase reagent for tin (IV) determination [19]. The determination of quercetin is typically performed with HPLC-UV [15,20,21], besides electrogenerated chemiluminescence (ECL) [22] and capillary electrophoresis (CE) [23]. Because of the existence of quercetins in nature at low concentrations, the complexity of the sample matrices and the structural similarity to other flavonols, selective sample preparation methods are necessary prior to chromatographic analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the existence of quercetins in nature at low concentrations, the complexity of the sample matrices and the structural similarity to other flavonols, selective sample preparation methods are necessary prior to chromatographic analysis. Preconcentration and/or separation of the compounds are frequently conducted by using SPE [20,21], in which new selective materials employing molecular recognition mechanisms might guarantee selective analyte separation from complex real world matrices. This mechanism can improve significantly the method specificity and sensitivity.…”
Section: Introductionmentioning
confidence: 99%